Proust and the visual - Aubert, Nathalie (Studies in Visual Cultures., 2013)
This collection of essays is aiming at capturing the rich and complex category of the "visual" both in Proust's novel itself (in its philosophical and stylistic implications) and beyond it, in other visual practices (cinema, painting, dance) inspired by the novel.